Mobile taxi booking application service’s continuance usage intention by users - Weng, Gooi Sai; Zailani, Suhaiza; Iranmanesh, Mohammad; Hyun, Sunghyup Sean (Elsevier, 2017)
The long-term development of a mobile booking taxi application service depends on the continued use of its passengers. The aim of this study is to investigate the determinants of the mobile taxi booking application service's continuance intention, using the technology continuance theory by including the perceived risk and subjective norms. The data were collected by surveying 387 users of the mobile taxi application service. The data were analysed by applying the partial least squares technique. The analysis showed that the technology continuance theory has extensive power to explain the continuance intention to use the mobile booking taxi application. Subjective norms also have a significant effect on the attitude of mobile booking taxi application users which represents an important contribution to technology continuance theory extension. The theoretical and practical significances of the study have been discussed.